2014
DOI: 10.1088/0953-4075/47/2/025004
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization study of Xe 5s: ionization cross sections and photoelectron angular distributions

Abstract: We report studies of photoelectron angular distribution and cross-section for photoionization of xenon 5s electrons using the relativistic multiconfiguration Tamm-Dancoff (MCTD) approximation. We find that MCTD provides a significantly improved agreement with experiment, compared to some of the other relativistic many body approximations such as the relativistic random phase approximation and the relativistic random phase approximation with relaxation, over the entire photon energy region bracketing the near-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 22 publications
2
19
1
Order By: Relevance
“…Unfortunately, there are only a few studies in which the RMCTD method has been tested. For example, it has been used to account for photoionization of a very few atoms, Mg and Be [13], Cd [30] and Xe [31] and photodetachment of a few negative ions [32,33]. The present study tests the applicability of the RMCTD to a rather highly correlated atom, atomic barium.…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, there are only a few studies in which the RMCTD method has been tested. For example, it has been used to account for photoionization of a very few atoms, Mg and Be [13], Cd [30] and Xe [31] and photodetachment of a few negative ions [32,33]. The present study tests the applicability of the RMCTD to a rather highly correlated atom, atomic barium.…”
Section: Introductionmentioning
confidence: 98%
“…The corresponding velocity gauge results (not shown) deviate from the experiment (Fahlman et al 1983) even stronger than RRPA with the parameter for Xe reaching nearly -1 near the CM. The strong e↵ect of the ground state correlation on the ns photoionization near the Cooper minimum can be understood from the multi-configuration expansion presented in (Aarthi et al 2014) for Xe. This expansion contains excitations in the following generic form: 5p 2 ⌫ 1/2 5p 4 µ 3/2 5d ⌫ 3/2 5d µ 5/2 , ⌫, µ = 0, 2, 4 As is seen from Equation (9), the 5d 3/2 bound state can be ionized to both the Ep 1/2 and Ep 3/2 continua whereas the 5d 5/2 state can only couple to the Ep 3/2 one.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…However, the nature of this deficiency A c c e p t e d M a n u s c r i p t has not been addressed and explained until recently. Aarthi et al (2014) suggested that this deficiency can be remedied by inclusion of (i) the ground state correlation and (ii) certain two-electron excitation and ionization channels. Indeed, the MCTD calculation for Xe (Aarthi et al 2014) is much closer to the experimental data (Fahlman et al 1983) than the RRPA, both for the cross-section and the parameter (right panels of Figure 1 and figure 2, respectively).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations